Role of Ultrasonography in Monitoring Chemotherapeutic Effects on Primary Thyroid Lymphoma: A Single-Center Retrospective Study - Shirong Liu; Ying Fu; Ligang Cui; Shumin Wang; Shi Tan (Medicina)
Background and Objectives: In this study, we assessed the utility of ultrasonography in monitoring the chemotherapeutic effects on primary thyroid lymphoma (PTL). Materials and Methods: This retrospective analysis included 17 patients with PTL who received chemotherapy from 2012 to 2022. The sonographic features were examined pre- and post-treatment using ultrasound (US) to monitor the treatment response at the first to second, third to fourth, and end cycles of chemotherapy and follow-up, and progression-free survival (PFS) and overall survival (OS) were analyzed. Results: The sonographic findings for all the patients indicated diffuse or nodular infiltration with markedly hypoechoic masses, and “stripe-shaped” high echoes and posterior acoustic enhancement were observed. Following one to two cycles of chemotherapy, a US examination revealed varying tumor reduction degrees and diminished blood flow signals. After three to four cycles of chemotherapy, the US demonstrated an evaluation efficacy comparable to that of PET-CT in cases in which the lesion had entirely disappeared postchemotherapy; however, its ability to differentiate between treatment response and residual lesions was less effective compared to that of PET-CT. After the end cycle of chemotherapy, the lesion sizes had significantly decreased compared to those at the baseline (p < 0.05). Postchemotherapy, Adler’s blood flow grades decreased significantly, with 80% graded as 0–1. Among the 10 patients with cervical lymph node enlargement, 70% showed reduced lesion sizes and blood flow signals. The cumulative 5-year PFS and OS rates were both 80% for the diffuse type and 82.5% and 78.8% for the nodular type, respectively (p > 0.05). Conclusions: US can be utilized to monitor the therapeutic response following chemotherapy for PTL, especially for early assessment and repeated dynamic monitoring, and can serve as a complementary follow-up method to PET-CT.